2021
DOI: 10.21037/jtd-21-1578
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction facilitates thoracoscopic anatomical partial lobectomy by an inexperienced surgeon: a single-institution retrospective review

Abstract: Background: This study aimed to evaluate the effect of three-dimensional (3D) interactive quantitative surgical planning on the outcome of video-assisted thoracoscopic surgery (VATS) anatomical partial lobectomy (APL), and to investigate the learning curve of 3D reconstruction-assisted VATS APL assisted. Methods: We retrospectively analyzed 156 cases of solitary pulmonary ground-glass opacity (GGO) lesions in patients who underwent 3D interactive quantitative VATS APL. Digital imaging and communications in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In our opinion, the systematic use of 3D-CT reconstructions, both in pre-operative and intraoperative settings, can reduce not only the likelihood of intraoperative complications related to interpretations of segmental anatomy but can also help to decrease operative time, because surgeons have already clearly "seen" the bronchovascular anatomy before surgery. We reported no intraoperative complications, and the surgical time of our preliminary tests were in line with literature results for segmentectomies performed with 3D reconstructions [21]. Nevertheless, we must remember that this paper reports only our preliminary findings, and improvements are ongoing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our opinion, the systematic use of 3D-CT reconstructions, both in pre-operative and intraoperative settings, can reduce not only the likelihood of intraoperative complications related to interpretations of segmental anatomy but can also help to decrease operative time, because surgeons have already clearly "seen" the bronchovascular anatomy before surgery. We reported no intraoperative complications, and the surgical time of our preliminary tests were in line with literature results for segmentectomies performed with 3D reconstructions [21]. Nevertheless, we must remember that this paper reports only our preliminary findings, and improvements are ongoing.…”
Section: Discussionsupporting
confidence: 86%
“…With 3D images, aspiring surgeons may familiarize themselves with lung anatomy and could approach segmental structures and variations in an interactive way, simulating surgical procedures by cutting the bronchovascular structures in the same order as they would in real surgery. Moreover, there is already evidence that 3D images might improve surgical residency training [21].…”
Section: Discussionmentioning
confidence: 99%
“…The high-quality 3D reconstructions rendered by modern CT-imaging techniques might also possess educational value in obtaining informed consent from patients regarding the surgical procedure they are subjected to. Also, evidence suggests it might improve surgical residency training ( 37 , 45 , 52 , 53 ). The latter was investigated by Zhang et al ( 46 ), who found evidence of faster learning of complex VATS procedures in surgical residents that used 3D reconstructions in their surgical preparation, compared to older surgeons that did not have these sophisticated techniques at their disposal, although age might have confounded these results.…”
Section: Resultsmentioning
confidence: 99%
“…Both in the simple and complex groups, the initial learning period showed a longer operative time, but intraoperative bleeding and postoperative complications were in a more acceptable range, which can be attributed to the correct preoperative 3D reconstruction and planning of the surgical procedure. Variations in vascular and bronchial structures may increase operative time and the risk of accidental bronchial injury, but with recent advances such as image processing and artificial intelligence 3D reconstruction allowing proof of the precise structure of the pulmonary arteries and veins, this allows surgeons to perform CSS more safely and effectively ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%